INTERNALISASI NILAI PELESTARIAN LINGKUNGAN MELALUI PEMBELAJARAN IPAS: ANALISIS PERSEPSI DAN SIKAP DAUR ULANG SISWA KELAS 5 SD NEGERI SALAM BABARIS 2 KABUPATEN TAPIN - Rindi Farianti; Irni Cahyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Environmental education is a vital component of sustainable development, particularly in primary education where foundational ecological values are established. This study aims to analyze and describe the process of planning, implementation, and evaluation in internalizing environmental conservation values through Natural and Social Science (IPAS) learning, as well as analyzing fifth-grade students' perceptions and recycling attitudes at SD Negeri Salambabaris 2, Tapin Regency. This research employed a qualitative approach with a descriptive case study design. The study subjects were selected using purposive sampling, consisting of 5 fifth-grade students out of 20 total students, along with the fifth-grade classroom teacher as the primary informant. Informant selection was based on criteria including active participation in IPAS learning, ability to articulate opinions, and representation of diverse student characteristics. Data were collected through passive participant observation, semi-structured in-depth interviews, and documentation analysis of instructional modules and student activities. Data analysis was carried out using the Miles and Huberman interactive model, comprising data collection, data reduction, data display, and conclusion drawing/verification. Data trustworthiness was maintained through technical triangulation. The results revealed three primary findings: (1) Instructional planning was conducted by integrating ecological values and 3R waste management principles into IPAS Module 8 ('Bumiku Sayang, Bumiku Malang'), formulating affective learning indicators, and preparing eco-media; (2) Learning implementation utilized Problem-Based Learning (PBL) with local environmental issues, outdoor learning, and direct recycling projects (converting plastic bottles and discarded water jugs into aesthetic plant pots); (3) Evaluation encompassed knowledge tests, affective observation rubrics, and project-based skills assessment. The internalization process successfully fostered students' transition from instrumental compliance to autonomous moral responsibility, evidenced by self-initiated classroom cleanliness, waste sorting habits, reduced single-use plastics, and sustained environmental empathy.